2020
DOI: 10.1111/ajps.12527
|View full text |Cite
|
Sign up to set email alerts
|

Winning Hearts and Minds in Civil Wars: Governance, Leadership Change, and Support for Violent Groups in Iraq

Abstract: The "hearts and minds" model of combating rebellions holds that civilians are less likely to support violent opposition groups if the government provides public services and security. Building on this model, we argue that a political event that raises popular expectations of future public service and security provision increases support for the government and decreases sympathy for violent opposition groups. To test this argument, we leverage a unique research design opportunity that stems from the unforeseen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Taking advantage of the staggered timing of survey enumeration, we identify combat events involving casualties of a troop-sending nation around the interview date specific to each individual respondent and specific to the nationality of the respondent. This design follows recent innovations in the study of domestic politics of international issues, including Mikulaschek, Pant and Tesfaye (2020) and Solodoch (2021). Consistent with the theoretical argument, we document that own-country casualties are associated with a worsening of the support for continued military intervention, while non-combat troop deaths have no discernible impact on support.…”
Section: Introductionsupporting
confidence: 75%
“…Taking advantage of the staggered timing of survey enumeration, we identify combat events involving casualties of a troop-sending nation around the interview date specific to each individual respondent and specific to the nationality of the respondent. This design follows recent innovations in the study of domestic politics of international issues, including Mikulaschek, Pant and Tesfaye (2020) and Solodoch (2021). Consistent with the theoretical argument, we document that own-country casualties are associated with a worsening of the support for continued military intervention, while non-combat troop deaths have no discernible impact on support.…”
Section: Introductionsupporting
confidence: 75%
“…Using the example of the Sunni minority in Iraq, Mikulaschek (2020) and his colleagues argue that the strategy of winning hearts and minds succeeded among the Sunni minority in 2014 after the government won the local population's confidence, especially in its ability to provide public services and security. Here, the Sunni minority's support for the jihadist rebels was significantly diminished, and the population's support shifted to the government (Mikulaschek et al, 2020, p. 78).…”
Section: Coin: Definition and Main Approachesmentioning
confidence: 99%
“…13 Mikulashek, Pant, and Tesfaye found that the expectation that the incoming Iraqi government would provide security to be an important factor in rising support for the government and declining support for insurgents. 14 Böhnke, Koehler, and Zürcher found in a longitudinal study in Afghanistan running from 2007-2015, that the provision of security was a key condition in non-combatants decision to attach their loyalty to the state. 15 Beth,Christia,and Enikolopov demonstrated in a study of the factors that drove support for the Afghan government that providing security to the population was a precondition for attracting support from the population.…”
Section: Existing Explanations For Civilian Support During Wartimementioning
confidence: 99%